The Influence of Workload on The Work Stress of Nurses in The Inpatient Room at Mitra Medika Amplas Hospital - Rahmawati Tarigan; Aida Sulisna; Andini Mentari Tarigan (International Archives of Medical Sciences and Public Health, 2022)
Introduction: Workload is the volume of work that is imposed on a person both physically and mentally and is his responsibility. Job stress is a condition of physical and psychological imbalance, which affects one's emotions, thought processes. Based on the results of the initial survey, nurses said that the large number of patients was not matched by the number of nurses which caused workload, a full room also resulted in workload, work stress experienced, namely patient complaints, uncooperative patient families and lack of equipment. Objectives: To identify and identify the effect of workload on nurses' work stress in inpatient rooms at Mitra Medika Hospital. Methods: This type of research uses a quantitative cross-sectional approach . The population and sample in this study used the Accidental Sampling Technique with a sample of 68 inpatient nurses. Results: Chi square test there is a significant relationship between the internal performance load variable and the work stress of nurses in the inpatient room of Mitra Medika Amplas Hospital with a p-value of 0.00 0 <0.05 and there is a significant relationship between the external performance load variable and work stress of nurses in the inpatient room of Mitra Medika Amplas Hospital with a p-value of 0.00 0 <0.05. Conclusion: Based on data analysis, there is an influence of internal and external workload on work stress experienced by nurses in the inpatient room of Mitra Medika Amplas Hospital. The advice that can be given is that it is hoped that the hospital management will pay attention to the workload of nurses again, by increasing the number of nurses in the inpatient room and conducting routine nursing performance evaluations in order to improve the quality of nursing care .